PEMBERDAYAAN MASYARAKAT MELALUI PENGEMBANGAN EKOWISATA DESA KARANGSONG, INDRAMAYU, JAWA BARAT - Zuyin Arwani (Program Studi Pengembangan Masyarakat Islam (PMI) FIDIKOM, UIN Syarif Hidayatullah Jakarta, 2021)
AbstractProgram community priorities mono years entitled “empowerment of community groups the Karangsong, Indramayu Regency in order to Increase the area of Mangrove Ecotourism is more better” is a program with the aim to improve the competitiveness of mangrove ecotourism in Karangsong to be worldwide. Involving the community in the management is a good step to increase the standard of living of the community of the village of Karangsong. Currently the team’s been doing year mono PPMP coordination between sustainable and office of coast of the CTF in Indramayu Regency. This coordination meetings discuss the activities that will be undertaken by a joint team of community and sustainable Beach, for doing pendapingan in the process of improving the competitiveness of mangrove ecotourism in Karangsong. The methods used to socializing and focus group discussion (FGD). The result of this socialization of society know the importance of mangrove ecosystems are maintained and the concept of ekoturisme can be done with the rule correctly, and create new attractions namely the program see the bird with a binocular. Concept of empowerment of the community need to be improved so that the group manager can be preserved more of the beach and the ecotourism mangrove can be better maintained and clean and can increase the arrival of tourists.Keywords: community empowerment; mangrove ecosystems; ecotourismAbstrakProgram Pengabdian kepada Masyarakat Prioritas mono tahun dengan judul “Pemberdayaan Kelompok Masyarakat Karangsong, Kabupaten Indramayu Guna Meningkatkan Kawasan Ekowisata Mangrove Lebih Baik” adalah program dengan tujuan untuk meningkatkan daya saing ekowisata mangrove di Karangsong agar bisa mendunia. Melibatkan masyarakat dalam pengelolaan merupakan langkah yang baik untuk meningkatkan taraf hidup masyarakat desa Karangsong. Saat ini tim PPMP mono tahun sudah melakukan koordinasi antara kelompok pantai lestari dan Dinas KKP di Kabupaten Indramayu. Pertemuan koordinasi ini membahas kegiatan yang akan dilakukan oleh tim bersama masyarakat dan kelompok pantai lestari, guna untuk dilakukannya pendapingan dalam proses peningkatan daya saing ekowisata mangrove di Karangsong. Metode yang digunakan sosialisasi dan fokus group diskusi (FGD). Hasil dari sosialisasi ini masyarakat tahu pentingnya ekosistem mangrove dijaga dan konsep ekoturisme dapat dilakukan dengan cara yang tepat, dan membuat aktraksi baru yaitu program melihat burung dengan binocular. Konsep pemberdayaan dari masyarakat perlu ditingkatkan agar kelompok pengelola pantai lestari bisa lebih banyak, dan kawasan ekowisata mangrove dapat terjaga lebih baik dan bersih dan bisa meningkatkan kedatangan wisatawan. Kata kunci: pemberdayaan masyarakat; ekosistem mangrove; ekoturismeDOI-